Penerapan Model Pembelajaran Numbered Head Together untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII di SMP N 35 Medan - Panggabean, Lili Yessi; Hasratuddin (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
This research aims: (1) to describe the improvement in mathematical problem solving abilities of class VIII students at SMP N 35 Medan through the application of the Numbered Head Together learning model and (2) to improve the mathematical problem solving abilities of class VIII students at SMP N 35 through the application of the Numbered Head learning model Together achieves classic completion. The subjects in this research were 28 students in class VIII-3 of SMP N 35 Medan after implementing the Numbered Head Together (NHT) learning model. This research is classroom action research (PTK), consisting of 2 cycles and per cycle carried out in 1 meeting. The data collection instruments used were observation sheets and mathematical problem solving ability tests. The results of this research show that there was an increase in the mathematical problem solving abilities of class VIII-3 students by 32.59 from the initial test carried out to cycle II after implementing the NHT model in the classroom. In cycle I, the average class score was 73.43 with classical completeness of 50%, and in cycle II the class average increased to 81.92 with classical completeness of 85.71%. Thus, it can be concluded that the application of the Numbered Head Together learning model can improve the mathematical problem solving abilities of class VIII-3 students at SMP N 35 Medan. Kata Kunci: Model Pembelajaran, Numbered Head Together, Kemampuan Pemecahan Masalah